Small molecule UCM05 inhibits HSV-2 infection via targeting viral glycoproteins and fatty acid synthase with potentiating antiviral immunity - Songshan Li; Minghan Li; Yantong Cai; Jun Xian; Rongrong Zhu; Chan Yang; Xin Zhang; Shuya Ren; Aijiao Yu; Shuwen Liu; Bin Yang (Virology Journal)
Abstract Herpes simplex virus type 2 (HSV-2) is a highly prevalent human pathogen worldwide that not only causes genital herpes but is also associated with severe health complications, such as neonatal infections and increased susceptibility to HIV. Currently, due to the lack of an effective HSV-2 vaccine and the emergence of more drug-resistant strains, there is an urgent need to develop effective, safe, and affordable anti-HSV-2 medications. The small molecule UCM05 is a novel inhibitor of fatty acid synthase (FASN) and filamentous temperature-sensitive protein Z (Ftsz), with antitumor and antibacterial effects. In this study, we found that UCM05 effectively inhibits both HSV-2 and acyclovir-resistant HSV-2 infections in vitro, significantly improves survival rates in HSV-2-infected mice, and effectively reduces viral titers in tissues. Further, we discovered that UCM05 destroys the membrane integrity of viral particles by directly binding with HSV-2 glycoproteins gB and gD and reduces viral replication by inhibiting viral protein synthesis and fatty acid synthesis. Additionally, UCM05 treatment promoted the generation of type I IFN related genes but does not result in an inflammatory cytokine storm triggered by HSV-2, and it also exhibited activity against co-infection with HIV-1/HSV-2, as well as infection with HSV-1. Overall, our research demonstrates that UCM05 can effectively inhibit HSV-2 infection both in vitro and in vivo. UCM05 represents a potential new antiviral drug against HSV-2.